Personajes teatrales que se escapan de las páginas de sus novelas: interpluritextualidad en el teatro de Mario Vargas Llosa - Chumacero Ancajima, Shirley Verónica (2024)
Interpluritextuality (or also intratextuality, autointertextuality), which builds a bridge between novels and theatre, is a unique characteristic of Vargas Llosa's fiction. Connecting his narrative and his theatre using the same characters is part of the totalizing desire that Vargas Llosa has expressed in his essays and interviews. This Balzacian search and ambition to encompass the totality of humanity meant that several of his theatrical characters were conceived years before in his narrative and recovered from it to take on a leading role in the theatre later on. This recurrence can be traced back to Vargas Llosa's literary conception itself; Pedro Camacho, Zavalita, la Chunga, Lituma and the unconquerables are part of the entourage of cultural self-demons that have driven the Nobel Prize winner's creative force to the point of achieving their own existence. They did not preexist the creator, they were born with him in the novel and became visible in dramatic art. In this line, we propose in the present study: to analyze how such characters were conceived in a novel and exorcised in its theater.